2017
DOI: 10.1103/physrevb.96.014437
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of the CrMnFeCoNi high-entropy alloy

Abstract: We present experimental data showing that the equiatomic CrMnFeCoNi high-entropy alloy undergoes two magnetic transformations at temperatures below 100 K while maintaining its FCC structure down to 3 K. The first transition, paramagnetic to spin glass, was detected at 93 K and the second transition of the ferromagnetic type occurred at 38 K. Field-assisted cooling below 38 K resulted in a systematic vertical shift of the hysteresis curves. Strength and direction of the associated magnetization bias was proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 74 publications
10
89
2
Order By: Relevance
“…In this limit, an effective spin S can be defined for each atom, and the entropy approximated as k B ln(2S 1 1). Although rigorous calculation of magnetic entropy is not yet available for HEAs, experimental information is available [76][77][78] owing to the possible application of HEAs in magnetic refridgeration. 21…”
Section: A Direct Methodsmentioning
confidence: 99%
“…In this limit, an effective spin S can be defined for each atom, and the entropy approximated as k B ln(2S 1 1). Although rigorous calculation of magnetic entropy is not yet available for HEAs, experimental information is available [76][77][78] owing to the possible application of HEAs in magnetic refridgeration. 21…”
Section: A Direct Methodsmentioning
confidence: 99%
“…The mechanical properties of HEAs have been extensively studied [12][13][14][15][16][17] but their functional properties are less explored. Most recent studies on functional properties of HEAs have addressed thermal, electrical, and magnetic properties, yet detailed studies on the underlying mechanisms are still rare [18][19][20][21][22][23][24][25][26]. While as an example for specific functional properties the resistive and superconducting properties of a TaNbHfZrTi HEA with a critical temperature of 7.3 K have been addressed [20], long term benefits could arise from HEAs with combinations of good mechanical and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies and models are scarce in the literature, and also for verification and validation of such models high-throughput and in-situ experiments are required. [129,130]; i: [131,132]; j: [133][134][135][136][137][138][139][140][141].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the vacancy significantly affects its surrounding local spin magnetic moment. In another study, DFT calculations and five different experimental methods were combined and utilized to determine the magnetic ordering in the CoCrFeMnNi MPE alloys [135]. Their first-principles calculations showed that interactions of Fe-located and/or Mn-located moments with the nearby magnetic structure may be responsible for the experimental macroscopic magnetization bias.…”
Section: Magnetic Propertiesmentioning
confidence: 99%